Politik Islam Indonesia dalam Perspektif Filsafat Politik Al- Mawardi - , Mohammad Alfuniam, S.Fil.I ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This is a literature study (library research), using the formal object of political philosophy, with its two material objects, first is thoughts on al-Mawardiâs politics listed in two of his masterpieces "Al-Ahkam As Sulthaniyyah: Principles of Organization of Islamic Countries" and " Adabud Dunya wa Din: Enjoyment of Life and World Religions